RADISH CULTIVARS BRED AT VNIISSOK AND THEIR USE - M. I. Fedorova; T. V. Zayachkovskaya (Овощи России)
On the base of comparative assessment and average data estimation from 2010 to 2015, the characteristics of 11 cultivars bred at VNIISSOK were described regarding yield capacity and its components, variation, interdependencies at two sowing terms winter,spring time, direction of selection and cultivar uses at cultivar maintaining breeding program. Cultivar 'Koroleva Margo' is rather used in breeding program for yield capacity and taste qualities. Cultivar 'Sonata' is a source of such features as early maturity, valuable biochemical content and low nitrate accumulation. Cultivar 'Sofit' is known to bear early maturity and simultaneous seed maturation. 'Ariya' is a source of cylindrical root shape and early maturation. Cultivar 'Teplichnyi Gribovskyi' is used in breeding program for early maturation and simultaneous seed maturation. Cultivar 'Feya' bearsresistance to bolting and valuable biochemical substances. Cultivar 'Variant' has such features as root density, ability to grow under low lighting, short-term storability.  Purple-red with white tips is a newmade cultivar 'Mavr' suitable for breeding program for valuable biochemical content, unusual root color, also bearing male sterile forms (MS) for heterosis hybrid breeding. Out of all cultivars regarded, 'Mokhovskiy' is only a genetic source to breed radish forms with edible leaves. The positive weak dependence was revealed between cultivar biochemical characteristics, root weight, dry matter  content, and nitrate content; whereas the positive middle dependence is revealed with sugar contents and negative dependence with ascorbic acid content. According to  iochemical characteristics, the best cultivar population as 'Ariya', 'Sonata' (ascorbic acid); Mavr, Sonata, Variant (dry matter, sugars) have been chosen. Cultivars 'Koroleva Margo', Pheya, Sonata, Sophit, Mokhovskiy are the initial breeding accessions for selection of new cultivar population, MS and MF lines needed for heterosis.